Comparative Qualitative Analysis of Women’s Football in the United States and England - Lippitt, Mona Kate (2017)
Purpose – The study compares women’s football in the United States and England whilst focusing on the attributions of the organizational structures, media influence, and cultural perceptions. Furthermore, the research explores the overall benefits through the implication of women’s football into society. Design/Methodology/Approach - The study utilized a qualitative semi-structured interview approach for data gathering. The data sample consisted of 13 female players and coaches from both the United States and England. The interviews were thematically analysed with a hybrid inductive-deductive coding style (Fereday & Muir-Cochrane, 2016) in which the creation of themes and subthemes were undertaken manually. Findings - The research discovered a higher degree of cross-national variation existing in the current perception and culture in relation to the structural foundations and influence of media. Research Limitations – Based upon a small sample of interviews, the demographics of respondents were primarily white, middle to high socioeconomic female footballers. In order to fully understand the criteria researched, a larger sample is required. Practical Implications – Through the examination of the historical context of women’s football and research of current idealized patterns of practice, the study addresses the degree in which business, media, and organizations can break through cultural, societal, and regulatory barriers. Thus, propelling and empowering future generations of female athletes.